Uji Aktivitas Antioksidan Kombinasi Ekstrak Umbi Bawang Tiwai (Eleutherine bulbosa (Mill) Urb) dan Rimpang Kunyit(Curcuma domestica Val.) - Yoni Miftahun Nafsiyah Agustin; Lisna Meylina; Yurika Sastyarina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
Bawang tiwai (Eleutherine bulbosa (Mill) Urb)a plant that originated from Kalimantan. This plant is traditionally used as a medicinal plant in the community. Bawang tiwai have bioactive compounds such as alkaloids, flavonoids, saponins which act as antioxidants. In addition bawang tiwai, turmeric (Curcuma domestica Val.)is a traditional medicinal plant used for seasoning and is a medicinal plant as antimicrobial, antioxidant, anti-tumor and anti-inflammatory. The aim of the research is to measure the antioxidant activity of the combination of extracts of bawang tiwai(Eleutherine bulbosa (Mill) Urb)and Turmeric (Curcuma domestica Val.). Antioxidant activity test used the DPPH (1,1-Diphenyl-2-picryl Hidrazil) measured absorption at a wavelength of 517 nm. Antioxidant activity was assessed based on% inhibition (IC50) which is the concentration of the sample solution is needed to reduce free radicals by 50%. The results obtained by measuring the antioxidant activity fromcombination extracts of IC50 was 185,118 ppm respectively.